WOMEN BEHIND WHEELS EXPLORING THE CLAY POTTERY FROM THIRUCHIGADI, NILGIRIS, TAMIL NĀDU - Ram, Anthima; Rao, Vishakha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Black pottery made by the women of Kota tribe of Nilgiri Hills holds a unique identity of their craft and craftmanship. A group of these women potters are names as “Kov” by the natives. This research study on Black pottery focuses on the traditional art of clay pottery in Thiruchigadi, a small town in Tamil Nadu’s gorgeous Nilgiris region. This study strives to reveal the historical significance, cultural context, and modern relevance of the age-old trade by focusing on the often-overlooked role of women potters. The extraordinary artistry, its evolution over ages and relevance of preserving the art and craft for the modern age. Adding lights on the sophisticated, unique, environmentally sustainable processes, designs, motifs, and the ritualistic essence that passed down through generations of female craftspeople through ethnographic observations, interviews, news articles, archival data, and research. The research shows these women’s strong sense of individuality, strong spirit, added contribution to the cultural skillset and a contribution towards retaining a thriving craft legacy by examining the socioeconomic dynamics and obstacles they encounter.